Copper (II) Oxide Nanoparticles as an Efficient Catalyst in the Azide-AlkyneCycloaddition - Amini, Mojtaba; Anbari, Alireza Pourvahabi; Ramezani, Sakine; Gautam, Sanjeev; Chae, Keun Hwa (WILEY-V C H VERLAG GMBH, 2016)
Copper (II) oxide nanorods and nanospheres were prepared and their structural, morphological, and electronic properties were investigated by X-ray diffraction analysis, X-ray absorption near edge structure, scanning electron microscope and transmission electron microscope. CuO nanoparticles efficiently cata-lyzes azide-alkyne 1,3-dipolar cycloaddition (CuAAC) reaction producing corresponding 1,2,3-triazole derivatives in excellent yields without use of any additives. The advantages of present protocol are mild reaction conditions, reusability of the catalyst, and applicability to a wide range of substrates.